A key review on security and privacy of big data: issues, challenges, and future research directions - Demiroll, Doygun; Das, Resul; Hanbay, Davut (Springer London Ltd, 2023)
Big data collection means collecting large volumes of data to have insight into better business decisions and greater customer satisfaction. Securing big data is difficult not just because of the large amount of data it handles, but also because of the continuous streaming of data, multiple types of data, and cloud-based data storage. Additionally, traditional security and privacy methods are insufficient due to large data volume, speed, and data from different sources. In this study, we focused on the security and privacy issues of big data. To this end, many related articles published in the literature have been extensively examined. Moreover, within the scope of big data, data security and privacy practices, current technologies, and methods are presented. Furthermore, we present an analysis of the security requirements of big data and the elimination of security vulnerabilities against cyber attacks.
Keywords: Big data analytics; Security; Privacy; Big data applications